2018
DOI: 10.1111/tra.12550
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between the endoplasmic reticulum and mitochondria by spontaneously inserting tail‐anchored proteins

Abstract: Tail-anchored (TA) proteins insert into their target organelles by incompletely elucidated posttranslational pathways. Some TA proteins spontaneously insert into protein-free liposomes, yet target a specific organelle in vivo. Two spontaneously inserting cytochrome b5 forms, b5-ER and b5-RR, which differ only in the charge of the C-terminal region, target the endoplasmic reticulum (ER) or the mitochondrial outer membrane (MOM), respectively. To bridge the gap between the cell-free and in cellula results, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…S7" type="url"/>). Taken together, these results are consistent with the notion that mitochondrial TA proteins do not use the TRC pathway (Figueiredo Costa et al, 2018). Hence, the effect on Fis1 steady-state levels may relate to another function of TRC40.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…S7" type="url"/>). Taken together, these results are consistent with the notion that mitochondrial TA proteins do not use the TRC pathway (Figueiredo Costa et al, 2018). Hence, the effect on Fis1 steady-state levels may relate to another function of TRC40.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, it is necessary to carefully distinguish which TA proteins can use the TRC pathway from the precursors for which it is essential. While the existing tools such as in vitro assays and knockout cells or organisms have begun to provide answers to these questions (Casson et al, 2017; Figueiredo Costa et al, 2018; Guna et al, 2018; Haßdenteufel et al, 2017; Lin et al, 2016; Norlin et al, 2016, 2018; Pfaff et al, 2016; Rivera-Monroy et al, 2016; Vogl et al, 2016), an approach is still lacking that would reveal which TA proteins do in fact use the TRC pathway when all targeting options are operational (i.e. without the compensatory effects often provoked by knockout strategies).…”
Section: Introductionmentioning
confidence: 99%
“…ExAC variants in this upstream region were rare (four unique variants between residues 158–193; Supplementary Table S2). Specific TRC40-dependent targeting to the ER/NE (rather than mitochondria or peroxisomes) requires negatively charged residues on the lumenal C-terminus (Costello et al, 2017; Figueiredo Costa et al, 2018). Emerin has two such residues, one of which is neutralized by variant p.E249G, identified in three individuals in ExAC (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this idea, it has been shown that ES1 is particularly cytotoxic against cancer cells when combined with proteasome inhibitors ( Wang et al., 2009 , Auner et al., 2013 ). Additional mechanisms that potentially contribute to the cytotoxic effects of ES1 are the impairment of both intracellular vesicular transport and membrane insertion of tail-anchored proteins ( Aletrari et al., 2011 , Naydenov et al., 2012 , Figueiredo Costa et al., 2018 ). Independently of targeting the ER-cytosol dislocation of proteins, ES1 also inhibits the co-translational translocation of nascent polypeptides into the ER, most likely by inhibiting Sec61 complexes both in cellula and in vitro ( Cross et al., 2009a ).…”
Section: Introductionmentioning
confidence: 99%